Learning from Covid-19 Pandemic: Lecturers' Perceptions on Creative Writing in Universities - Mohammad Ilyas (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this study is to describe in depth about three major themes, namely: lecturers' perceptions of strategies to improve student competence in creative writing learning in universities, the ability to cite using application technology and students' ability to argue and absorb students in creative writing learning in universities. The method used is qualitative research with a phenomenological approach, equipped with a literature study of the latest texts that are relevant to the research theme. Based on the results of data analysis and discussion, it can be concluded that first, the lecturer's strategy in teaching creative writing is carried out by developing ideas starting from prewriting to improving students' creative writing. Second, the majority of students have been able to do citations correctly by using citation technologies such as Mendeley, Zotero, and Endnote, paraphrasing, and selecting important ideas. Third, students have been able to describe high-level reasoning in improving the quality of their writing so that it is more useful for the development of science and technology as well as improving human welfare. Creative writing can be trained when students take research methodology courses, proposal seminars, and creative writing training.